Enantioselective Total Synthesis of the Putative Biosynthetic Intermediate Ambruticin J. Issue 43 (27th May 2021) - Trentadue, Kathryn; Chang, Chia‐Fu; Nalin, Ansel; Taylor, Richard E.
Abstract: The family of anti‐fungal natural products known as the ambruticins are structurally distinguished by a pair of pyran rings adorning a divinylcyclopropane core. Previous characterization of their biosynthesis, including the expression of a genetically modified producing organism, revealed that the polyketide synthase pathway proceeds via a diol intermediate, known as ambruticin J. Herein, we report the first enantioselective total synthesis of the putative PKS product, ambruticin J, according to a triply convergent synthetic route featuring a Suzuki‐Miyaura cross‐coupling and a Julia‐Kocienski olefination for fragment assembly. This synthesis takes advantage of synthetic methodology previously developed by our laboratory for the stereoselective generation of the trisubstituted cyclopropyl linchpin. Abstract : First total synthesis : A putative intermediate in ambruticin biosynthesis was prepared by a convergent route using a trisubstituted cyclopropyl linchpin. The stereochemical assignment has been confirmed and incorrect spectral data have been updated. Access to this material will enable studies of the post‐PKS processing that leads to ambruticin structures and aid greater understanding of their potent anti‐fungal activity.